Typifications in Epidendrum species (Laeliinae, Orchidaceae) endemic to Brazil - Pessoa, Edlley M.; Zocal, Kelvin H.; Feitoza, Lucas H.j.; Rondon-Anjos, Marcos V.; Pinho, Max F.; Ribeiro, Murilo G.; Cabral, Thainá P.s.; Koch, Ana K. (Phytotaxa, 2024)
During ongoing studies of the Brazilian species of Epidendrum, we determined that some names needed formal typification. Lectotypes for E. brevicolle, E. caldense, E. campestre, E. cinnabarinum, E. cooperianum E. goebelii, E. henschenii, E. longispathum, E. longispathum, E. paulense, E. revolutum, and E. setiferum, and an epitype for E. cooperianum are designated here. We provide discussions of the history of the names linked to each species.